PRODUKSI DAN PERSEPSI KOSAKATA ANAK USIA 4 SAMPAI DENGAN 5 TAHUN DENGAN BERLATAR BELAKANG ORANG TUA BERBEDA BAHASA IBU DI DESA KELUNCING KECAMATAN KASEMEN - Iin Indriyani; Asep Muhyidin; Sundawati Tisnasari (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2022)
The background of this research is based on the context of language acquisition in children with the aim of explaining children’s language and vocabulary acquisition in the field of phonology in the process and perception of vocabulary for children aged 4 to 5 years with different mother tongue backgrounds in Keluncing Village, Kasemen District. This research uses descriptive qualitative method. As for the data collection techniques that the researchers used, namely library research techniques, documentation methods, recording methods, listening methods, and note-taking methods. The source of data in this study, namely the vocabulary of children aged 4 to 5 years with parents’ backgrounds of different mother tongues. The data in this study are in the form of utterances or words in the field of phonology which consist of omission and change of phonemes. The data found in the speech of children spoken in children aged 4 to 5 years. Based on data analysis, the data obtained by the researchers were 38 data on vocabulary or words spoken by children in the field of phonology. Based on the results of data analysis consisting of several parts, the following conclusions are obtained from the data obtained: 1) initial phoneme disappearance of 7 data, 2) middle phoneme disappearance of 3 data, 3) initial phoneme change of 10 data, 4) middle phoneme change of 8 data , 5) 5 data of final phoneme changes, and 6) 5 data of missing and changing phonemes in one sentence.